2011
DOI: 10.1111/j.1439-0418.2011.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐release diet effect on field survival and dispersal of Anastrepha ludens and Anastrepha obliqua (Diptera: Tephritidae)

Abstract: The effect of pre‐release diets on starvation resistance, field survival and dispersal of sterile Anastrepha ludens and Anastrepha obliqua fruit flies was investigated. Protein‐enriched diets resulted in reduced longevity under laboratory and field conditions. Flies exposed to a combination of sugar and fresh mango fruit pulp showed greater longevity and field survival. Release–recapture experiments showed that this mango plus sugar diet resulted in the greatest trap capture and the longest life expectancy whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…However, Barry et al (2007) reported that the ability of the sterile flies to locate and feed on protein and carbohydrate sources in the field may be more important for survival than the type of food supplied before the release. Survival times in the field after release for A. ludens have been reported to be 4.7 d (Utges et al 2011) and 5.7 d (Hernández et al 2007), which are within the range reported in this study for both strains. For C. capitata, Gavriel et al (2012) reported that released adults rarely survived more than 5 d. These survival times are the minimum amount of time needed for the sterile males to reach sexual maturity, and the ability of sterile flies to survive until sexual maturity under field conditions is important for the successful use of the SIT (Thomas & LoeraGallardo 1998;Gómez-Cendra et al 2007).…”
Section: Discussionsupporting
confidence: 70%
“…However, Barry et al (2007) reported that the ability of the sterile flies to locate and feed on protein and carbohydrate sources in the field may be more important for survival than the type of food supplied before the release. Survival times in the field after release for A. ludens have been reported to be 4.7 d (Utges et al 2011) and 5.7 d (Hernández et al 2007), which are within the range reported in this study for both strains. For C. capitata, Gavriel et al (2012) reported that released adults rarely survived more than 5 d. These survival times are the minimum amount of time needed for the sterile males to reach sexual maturity, and the ability of sterile flies to survive until sexual maturity under field conditions is important for the successful use of the SIT (Thomas & LoeraGallardo 1998;Gómez-Cendra et al 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Crowded conditions, however, can cause dispersal movements to farther distances (Froerer et al 2010). The vegetation density at the release site is another factor that may influence the dispersal of adult flies as was shown for A. ludens by Utges et al (2011).…”
Section: Discussionmentioning
confidence: 92%
“…Life span of sterile males can be improved by providing suitable diet after emergence. Sterile adults of A. ludens and A. obliqua fed prior to release with a combination of sugar and fresh mango fruit pulp showed longer field survival than those fed with protein-enriched diets (Utges et al 2011). However, Barry et al (2007) reported that the ability of the sterile flies to locate and feed on protein and carbohydrate sources in the field may be more important for survival than the type of food supplied before the release.…”
Section: Discussionmentioning
confidence: 97%
“…The large scale and sustained application of SIT has been a key factor to maintain and expand the pest free areas (Liedo, ), and importantly, their also had gathered data of how SIT efficiency could be enhanced. While male life expectancy in the laboratory has been observed between 39 and 130 days (Carey et al., , ; Liedo, Carey, Celedonio, & Guillen, ; Tejeda et al., ), in field evaluations, where variable environmental conditions prevails, life expectancy oscillate around 2–10 days (Flores et al., ; Hernández, Orozco, Breceda, & Domínguez, ; Thomas & Loera‐Gallardo, ; Utgés, Vilardi, Oropeza, Toledo, & Liedo, ). The contrasting male life expectancies between laboratory and field indicate the possibility that sterile males are exposed to stress once released in the field.…”
Section: Introductionmentioning
confidence: 99%